Assessing the Impact of Director Characteristics on Firm Performance in the Banking and Financial Sector : U.K. and USA - Alam, Zakiul (2015)
Poor Corporate Governance practices by firms are thought to have largely influenced what is widely considered the worst economic recession since the depression of the 1930’s, leading global financial centres of New York and London in the midst of this extraordinary bank-crippling crisis. In the wake of the financial crisis, this investigation considers how characteristics defining the board of directors may play a role in preventing future corporate collapses by influencing financial performance. This study looks at the composition and characteristics of board directors based on a sample of 232 firm-year observations for the largest companies listed on the highly volatile U.K. (FTSE) and U.S (NYSE) stock exchanges,. The particular board characteristics investigated were: gender equality, executive compensations, managerial-ownership, transparency and disclosures, independence of the board as well as firm leadership. Modelled within the governance framework set out by the Organisation for Economic Co-operation and Development (OECD); this study examines the relationship between key corporate governance mechanisms concerning the board directors and their effects on firm performance. Findings are based on data gathered from the fiscal years 2012 and 2013, as the global economy enters the midst of economic recovery. Multiple regression analyses using SPSS show that the influence of board of director characteristics varies significantly between the U.S and U.K. markets. Research findings show that in the U.S, an increased in insider ownership, greater gender diversity on the board, combined CEO-Chair roles, smaller board sizes and increases in CEO compensation all positively influence the regression model of director characteristics in relation to performance. In the U.K, younger CEOs and those exhibiting lower turnover, as well as separation of management and ownership and a greater proportion of executive directors on the board are significant to increased company returns.